2013
DOI: 10.1007/s11356-013-1972-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective utilization of dichloromethane by a newly isolated strain Methylobacterium rhodesianum H13

Abstract: An effective dichloromethane (DCM) utilizer Methylobacterium rhodesianum H13 was isolated from activated sludge. A response surface methodology was conducted, and the optimal conditions were found to be 4.5 g/L Na2HPO4·12H2O, 0.5 g/L (NH4)2SO4, an initial pH of 7.55, and a temperature of 33.7 °C. The specific growth rate of 0.25 h(-1) on 10 mM DCM was achieved, demonstrating that M. rhodesianum H13 was superior to the other microorganisms in previous investigations of DCM utilization. DCM mineralization parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These regions may help to enhance adaptability and adhesion of the strain MB200 to surrounding environment ( Supplementary Table S2 ). The capacity to grow in the presence of dichloromethane (DCM) has been demonstrated in M. rhodesianum H13 [ 22 ]. However, the strain MB200 cannot grow on DCM, and the dcm gene cluster was not present in the genome of the strain MB200.…”
Section: Resultsmentioning
confidence: 99%
“…These regions may help to enhance adaptability and adhesion of the strain MB200 to surrounding environment ( Supplementary Table S2 ). The capacity to grow in the presence of dichloromethane (DCM) has been demonstrated in M. rhodesianum H13 [ 22 ]. However, the strain MB200 cannot grow on DCM, and the dcm gene cluster was not present in the genome of the strain MB200.…”
Section: Resultsmentioning
confidence: 99%
“…Methylene chloride had the highest content. Methylene chloride has a sweet taste and chloroform-like odor (Wang et al, 2022), is prevalent in water, and is toxic and a hazardous compound (Chen et al, 2013;Hammoud et al, 2021). Hendra et al (2021) extracted dichloromethane from dragon fruit peel and showed that dichloromethane has high antiplasmodial activity.…”
Section: Volatile Substances In Sv Crayfish Meat During Refrigerationmentioning
confidence: 99%
“…GSTs with known crystal structures can be used as templates for the prediction of DCM dehalogenase catalytic mechanism [23][24][25]. In our previous work, the DCM dehalogenase gene sequence was obtained from M. rhodesianum H13, which is a highly efficient DCM-degrading bacterium [26]. The specific activity of DCM dehalogenase from recombinant bacteria Escherichia coli BL21(DE3)-pET28b(þ)-dcm was detected as 0.00686 ± 0.00005 U/ mg, three times greater than from wild-type M. rhodesianum [27].…”
Section: Introductionmentioning
confidence: 99%